Which people with severe asthma attend pulmonary rehabilitation?: Insights from the German Asthma Net - Jarosch, Inga; Schneeberger, Tessa; Holtdirk, Annette; Gloeckl, Rainer; Kroll, Daniela; Buhl, Roland; Hamelmann, Eckard; Idzko, Marco; Taube, Christian; Milger, Katrin; Skowasch, Dirk; Schulz, Christian; et al. (ERJ Open Research, 2025)
Many people with severe asthma do not achieve complete asthma control and suffer from persistent symptoms such as dyspnoea and/or fatigue, difficulty performing work and daily activities, and/or frequent exacerbations. As a result, people with asthma often experience impaired quality of life, reduced lung function and exercise intolerance. Asthma is also a condition with a significant economic burden on society, which increases with poor disease control and greater disease severity.
Gesehen am 28.10.2025